Disruption of the Trichoderma reesei gul1 gene stimulates hyphal branching and reduces broth viscosity in cellulase production. (10th February 2021) - Zhao, Qinqin; Liu, Qin; Wang, Qi; Qin, Yuqi; Zhong, Yaohua; Gao, Liwei; Liu, Guodong; Qu, Yinbo
Abstract: Hyphal morphology is considered to have a close relationship with the production level of secreted proteins by filamentous fungi. In this study, the gul1 gene, which encodes a putative mRNA-binding protein, was disrupted in cellulase-producing fungus Trichoderma reesei . The hyphae of Δ gul1 strain produced more lateral branches than the parent strain. Under the condition for cellulase production, disruption of gul1 resulted in smaller mycelial clumps and significantly lower viscosity of fermentation broth. In addition, cellulase production was improved by 22% relative to the parent strain. Transcriptome analysis revealed that a set of genes encoding cell wall remodeling enzymes as well as hydrophobins were differentially expressed in the Δ gul1 strain. The results suggest that the regulatory role of gul1 in cell morphogenesis is likely conserved in filamentous fungi. To our knowledge, this is the first report on the engineering of gul1 in an industrially important fungus.